Persepsi Mahasiswa terhadap Problem Based Learning di Mata Kuliah Reading For Academic Purposes - Yunita Hatibie (Pascasarjana, Universitas Negeri Gorontalo, 2025)
Problem Based Learning in Reading for Academic Purposes require students’ critical thinking to analyze, collaborate, engagement, solve the problem and self-directed study to the students. This research explored the students’ perception towards Problem Based Learning in Reading for Academic Purposes. Descriptive qualitative approach is used in this research which used semi-structured interviews with third-year English Department students who had Problem Based Learning in Reading for Academic Purposes. This research used Thematic Analysis to revealed the students’ perception on Problem Based Learning in Reading for Academic Purposes. It shown that students have positive perceptions of Problem Based Learning in Reading for Academic Purposes. Students reported that PBL is engaging and meaningfull approach to enhance Reading for Academic Purposes. PBL effectively encourages active participation, improves text comprehension, and fosters learning motivation through relevant and meaningful tasks. Students perceive improvement in critical thinking, analysis, and the ability to solve complex problems within academic texts. Collaboration within groups was also found to enhance their communication and teamwork skills. Many students find group dynamics challenging, requiring strong facilitation to be effective. Supporting factors identified include the use of authentic reading materials, opportunities for discussion and reflection, and the instructor's role as a supportive facilitator. Students appreciate when PBL is implemented with scaffolding, as they often face difficulties with the heavy workload, need for extensive outside research, and time management. Meanwhile, several challenges were also noted, such as limited learning time, uneven group contributions, varying reading abilities among group members, and difficulties in understanding academic vocabulary. Students feel more responsible for their own learning process, which boosts their confidence in tackling difficult academic materials. The findings suggest that while PBL is effective in enhancing reading for academic purposes and promoting student-centered learning, its successful implementation requires careful planning, scaffolding strategies, and continuous support from instructors to overcome the identified constraints.